Current issues in managing men with lower urinary tract symptoms in primary care. Issue 10 (20th September 2013) - Chapple, C. R.; Osman, N. I.
<x xml:space="preserve">Abstract</x> Linked Comment: Coyne et al. Int J Clin Pract 2013; 67: 1015–33.